Porcine Viruses : From Pathogenesis to Strategies for Control - Zakaryan, Hovakim (Caister Academic Press, 2019)
This book provides a comprehensive review of the current knowledge of the most important porcine viruses written by prominent scientists who have made great contributions in their respective fields of expertise. Topics include: African swine fever virus, classical swine fever virus, foot-and-mouth disease virus, porcine circovirus, porcine epidemic diarrhea virus, porcine parvovirus, porcine reproductive and respiratory syndrome virus, and swine vesicular disease virus. Each chapter covers the current knowledge on epidemiology, pathogenesis, virus biology, diagnosis, and prevention and control.